The Anti-inflammatory Mediator Resolvin E1 Protects Mice Against Lipopolysaccharide-Induced Heart Injury - Zhang, Jishou; Wang, Menglong; Ye, Jing; Liu, Jianfang; Xu, Yao; Wang, Zhen; Ye, Di; Zhao, Mengmeng; Wan, Jun (Frontiers in Pharmacology, 2020)
Abstract Background: Sepsis-induced cardiomyopathy (SIC) is a common severe complication of sepsis that contributes to mortality. SIC is closely associated with excessive inflammatory responses, failed inflammation resolution and apoptotic damage. Resolvin E1 (RvE1), an omega-3 polyunsaturated fatty acid (PUFA)-derived metabolite, has been reported to exert anti-inflammatory or proresolving activity in multiple animal models of inflammatory disease. However, the therapeutic potential of RvE1 in SIC remains undetermined, which was, therefore, the aim of the present study. Methods: C57BL/6J mice were randomly divided into three groups: control, LPS and LPS + RvE1. Echocardiography, western blotting, QRT-PCR and histological analyses were used to evaluate cardiac function, myocardial inflammation and the underlying mechanisms. Results: The RvE1-injected group showed improved left ventricular function and reduced serum LDH and CK-MB levels. Compared to LPS treatment alone, RvE1 treatment inhibited the infiltration of neutrophils and macrophages into the heart and spleen and suppressed the secretion of proinflammatory cytokines, including IL-1β, IL-6 and MCP-1, in the heart. We also observed that the activation of the MAPK and NF-κB signaling pathways was blocked by RvE1 treatment, and this inhibition contributed to the improvement in the inflammatory response induced by LPS. RvE1 inhibited LPS-induced M1 macrophage polarization and promoted macrophage polarization toward the M2-like phenotype in both the heart and spleen. In addition, LPS administration dysregulated cyclooxygenase (COX) and lipoxygenase (LOX)in heart, which were rectified by RvE1 treatment. RvE1 also reduced myocardial apoptosis rate in response to LPS-induced heart injury. Conclusion: RvE1 protects the heart against SIC possibly through the inhibition of the MAPK and NF-κB inflammatory signaling pathways, modulation of macrophage polarization, reduction in myocardial apoptosis and activation of the inflammation resolving response. RvE1 may be a novel lipid mediator for the treatment of SIC.